Gastric Glomus Tumor: A Rare Cause of Upper Gastrointestinal Bleeding - Yoshinori Handa; Mikihiro Kano; Mayumi Kaneko; Naoki Hirabayashi (Case Reports in Surgery)
A 24-year-old woman was referred to our department because of melena. These symptoms combined with severe anemia prompted us to perform an emergency upper endoscopy, which showed bleeding from an ulcerated 30 mm submucosal tumor in the gastric antrum. A computed tomography scan revealed a homogeneously enhanced mass, and endoscopic ultrasonography identified a well-demarcated mass in the third and fourth layers of the gastric wall. Because analysis of the possible medical causes remained inconclusive and the risk of rebleeding, laparoscopy-assisted gastric wedge resection was performed after administration of 10 units of red cell concentrate. Histological and immunohistological analysis revealed the tumor to be a gastric glomus tumor. Gastric submucosal tumors remain challenging to diagnose preoperatively as they show a variety of radiologic and clinicopathologic features and are associated with the risk of bleeding upon biopsy, as is indicated in the guidelines for gastric submucosal tumors. Gastric glomus tumors characteristically present with exsanguinating gastrointestinal hemorrhaging that often requires blood transfusion. Additionally, gastric submucosal tumors typically occur in elderly patients; however, this case involved a young patient who was 24 years old. Here, we describe this case in order to identify features that may aid in early differentiation of gastric submucosal tumors.